Transformasi penyiaran televisyen melalui internet: kajian perhubungan kepuasan terhadap pengguna remaja - Hashim, Hasrul; Omar, Bahiyah (Penerbit UKM, 2011)
The emergence of Internet had brought a lot of changes in the mass media landscape. The conventional media had moved to a digital format and formed a media convergence that can attract audience’s interests especially the youths. This study chose a new medium that resulted from the combination of Internet and television, namely television portal to assess the levels of gratification of the medium usage among youths. Assessment made by exploring the relationship between the gratification sought (GS) and the gratification obtained (GO) for four measures of gratification, namely the need to obtain information, entertainment, interpersonal utility and also interactivity. This study also assessed the gratification that is acquired between the use of two television portal; RTM as a public broadcasting station and TV3 as a private broadcasting station. The findings showed there is a significant relationship between GS and GO for all four measures of gratification in this study. This study concluded with suggestion to RTM to improve the weaknesses that was identified in the effort to exploit the new media in order to capture and attract youth audience to expose them with the RTM’s programs.